Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2012
DOI: 10.1016/j.chiabu.2011.11.008
|View full text |Cite
|
Sign up to set email alerts
|

Parent emotional expressiveness and children's self-regulation: Associations with abused children's school functioning

Abstract: Objective Identifying factors associated with school functioning of abused children is important in prevention of long-term negative outcomes associated with school failure. The purpose of this study was to examine the degree to which parent emotional expressiveness and children's self-regulation predicted early school behavior of abused children. Methods The sample included 92 physically abused children ages 4-7 and one of their parents (95.7% mothers). Parents completed a measure of their own emotional exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(17 citation statements)
references
References 70 publications
(88 reference statements)
0
15
0
1
Order By: Relevance
“…In summary, the current study found that maternal experiences of childhood maltreatment moderated several aspects of infant‐mother cortisol responses during a mild stress procedure. The extant literature indicates that children of mothers who have experienced childhood maltreatment show a range of deleterious outcomes, including alterations in brain volume at birth (Moog et al, 2018), self‐regulation difficulties (Delker et al, 2014; Haskett et al, 2012), and elevated rates of developmental psychopathology (e.g., Plant et al, 2018). Dysregulation in the infant stress response system may be one key mechanism in the intergenerational transmission of the effects of MCM (Buss et al, 2017; Moog et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…In summary, the current study found that maternal experiences of childhood maltreatment moderated several aspects of infant‐mother cortisol responses during a mild stress procedure. The extant literature indicates that children of mothers who have experienced childhood maltreatment show a range of deleterious outcomes, including alterations in brain volume at birth (Moog et al, 2018), self‐regulation difficulties (Delker et al, 2014; Haskett et al, 2012), and elevated rates of developmental psychopathology (e.g., Plant et al, 2018). Dysregulation in the infant stress response system may be one key mechanism in the intergenerational transmission of the effects of MCM (Buss et al, 2017; Moog et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Climate includes such factors as parenting styles (i.e., responsive and warm versus harsh and dismissing), family expressiveness, particularly in the case of high levels of negativity, and the emotional quality of the marital relationship (Maughan, Cicchetti, Toth, & Rogosch, 2007). Climates that are unpredictable and negative are linked to children displaying high levels of emotional reactivity to challenges and poor regulation across a range of situations (Eisenberg et al, 1998; Haskett, Stelter, Proffit, & Nice, 2012). Of note, most of the research on socialization has been done with community samples – not samples at high risk for disturbed parent-child relationships and poor regulation.…”
Section: Socialization Of Self-regulationmentioning
confidence: 99%
“…[38] Previous research has documented a benefit of expressive writing as a coping intervention in college students, patients dealing with illness, and individuals who have experienced a natural disaster. [41] Other populations who have utilized expressive writing as an intervention include those that have a change in mental or physical well-being, [38,43] have experienced abuse, [44] or a traumatic experience, [45] and go through school transitions. [46] Within healthcare, expressive writing interventions has been utilized in medical education, [47] but has yet to be thoroughly studied in nursing, with only a few studies to date, and none with the specific intention of improving distress with using only expressive writing as the intervention.…”
Section: Expressive Writingmentioning
confidence: 99%